An ubiquitous smart guitar system for collaborative musical practice. Issue 4 (8th August 2019) - Turchet, Luca; Barthet, Mathieu
ABSTRACT: Ubiquitous music (UbiMus) proposes to study how social interaction with mobile and distributed technologies can converge to form novel creativity support tools and music artistic practices. A recent field overlapping with UbiMus is the Internet of Musical Things, which refers to ecosystems of interconnected embedded computers (Musical Things) enabling users to produce, interact with or experience musical content. Musical Things embed electronics, sensors, data forwarding and processing software into physical or virtual objects. Smart musical instruments (SMIs) are an emerging class of Musical Things provided with capabilities of capturing and receiving data supporting instrumental musical practice. Due to their portability and self-containdeness, SMIs enable novel ubiquitous interactions between performers of acoustic and digital musical instruments. After a review of current trends in SMI research, we propose an ubiquitous smart guitar system which uses the guitar as a hub for collaborative music making. We then present a survey conducted with 18 performers to assess the usability, creativity support and engagement with the system. Results show a positive emotional engagement with the system which overall was found easy to use and novel. We also discuss several barriers to creative interaction related to the size of the user interface, creative agency and personalisation.